2015
DOI: 10.1063/1.4923049
|View full text |Cite
|
Sign up to set email alerts
|

Particle shape inhomogeneity and plasmon-band broadening of solar-control LaB6 nanoparticles

Abstract: An ensemble inhomogeneity of non-spherical LaB 6 nanoparticles dispersion has been analyzed with Mie theory to account for the observed broad plasmon band. LaB 6 particle shape has been characterized using small-angle X-ray scattering (SAXS) and electron tomography (ET). SAXS scattering intensity is found to vary exponentially with exponent À3.10, indicating the particle shape of disk toward sphere. ET analysis disclosed dually grouped distribution of nanoparticle dispersion; one is large-sized at small aspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 57 publications
1
35
0
Order By: Relevance
“…The authors developed a model which goes beyond size and shape inhomogeneity with the aim to address variations that are primarily ascribed to dopant desorption on the NC surface and decrease in oxygen vacancies in each NC. [20] In plasmonic nanostructures the study of the quantum plasmon has attracted attention in recent years, addressing the discretization of the energy levels for very small sizes, opposed to the band type character usually observed. [218] In degenerately doped nanostructures that are small enough to support quantum confinement (i.e.…”
Section: Fundamental Optical Phenomena In Degenerate Semiconductor Namentioning
confidence: 99%
See 1 more Smart Citation
“…The authors developed a model which goes beyond size and shape inhomogeneity with the aim to address variations that are primarily ascribed to dopant desorption on the NC surface and decrease in oxygen vacancies in each NC. [20] In plasmonic nanostructures the study of the quantum plasmon has attracted attention in recent years, addressing the discretization of the energy levels for very small sizes, opposed to the band type character usually observed. [218] In degenerately doped nanostructures that are small enough to support quantum confinement (i.e.…”
Section: Fundamental Optical Phenomena In Degenerate Semiconductor Namentioning
confidence: 99%
“…[9] All these NCs have intense resonances in the mid to near IR due to plasmonic absorption. Additionally, NCs of other materials were found to show NIR plasmonic response, such as colloidal GeTe NCs, [18] LaB 6 NCs, [19,20] and Gd doped Prussian Blue. [21] Degenerately doped semiconductor NCs form an exceptional case, as high levels of doping can be reached, leading to degeneracy of the doping levels.…”
Section: Introductionmentioning
confidence: 99%
“…[ 10 , 11 , 12 ] Metal hexaborides (MB 6 ) are being sought after for these applications, and with lanthanum hexaboride (LaB 6 ) absorbing in the middle of this range (~1000 nm) [ 13 , 14 ] we focus our efforts here on the tuning of LaB 6 . It has already been shown that changing the particle size of LaB 6 nanoparticles offers a means of controlling the plasmon [ 15 , 16 ] and that these particles may be incorporated into polymers to make films [ 17 , 18 ]. Though some work has been done on LaB 6 to study how La vacancies influence vibrational energies [ 19 ] and how doping impacts the thermionic power [ 20 , 21 ], there is a potential link between doping content and vacancies in LaB 6 that has gone unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Whether morphological limitations are due to the chemistry itself or if low temperature methods simply need additional time to study has yet to be determined. The shape of LaB 6 nanoparticles tends to be described as generic nanoparticles (assumed spheres) versus cubes [56,77] (Figure 6A) or as nanowires [78,79,80], but to our knowledge only two publications to date tie plasmonics to varying particle shape [81,82].…”
Section: Controlling the Plasmon Of Lab6mentioning
confidence: 99%
“…The Mie integration method is also an effective means of estimating optical properties of nanoparticles of changing sizes and shapes [83]. For LaB 6 , it was found that increasing the aspect ratio of spheroids can enhance the LSPR properties in the NIR [81]. In oblate spheroids, decreasing the aspect ratio has the effect of red-shifting the LSPR, and can significantly broaden the absorbance peak (Figure 6C).…”
Section: Controlling the Plasmon Of Lab6mentioning
confidence: 99%